CHARACTERISTICS OF THE STATE AND PROSPECTS OF DEVELOPMENT OF THE HUNTING FARM OF THE SEVERNY STATE FARM OF THE ANABAR DISTRICT OF YAKUTIA IN THE SECOND HALF OF THE 1980-S - EARLY 1990-S (BASED ON FIELD RESEARCH MATERIALS) - Sannikova, Yana Mikhailovna (Agrarian History, 2022)
In the article, based on the materials of the project of on-farm hunting management of the state farm "Severny", the main characteristic of hunting is considered, taking into account the entire complex of the state farm economy, on the eve of the beginning transformations in the agricultural sector in the early 1990s. It is shown exactly how the work on the project of on-farm hunting management was organized at the turn of the 1980s - 1990s. The documents of the hunting farm of the state farm, its lands, the device, the personnel of hunters and the process of their direct preparation for fishing for the historical reconstruction of the traditional economic activity of the indigenous population in the studied period are analyzed.